The Sexunzipped Trial: Young People's Views of Participating in an Online Randomized Controlled Trial - Nicholas, Angela; Bailey, Julia V; Stevenson, Fiona; Murray, Elizabeth (JMIR Publications, 2013)
BackgroundIncidence of sexually transmitted infections (STIs) among young people in the United Kingdom is increasing. The Internet can be a suitable medium for delivery of sexual health information and sexual health promotion, given its high usage among young people, its potential for creating a sense of anonymity, and ease of access. Online randomized controlled trials (RCTs) are increasingly being used to evaluate online interventions, but while there are many advantages to online methodologies, they can be associated with a number of problems, including poor engagement with online interventions, poor trial retention, and concerns about the validity of data collected through self-report online. We conducted an online feasibility trial that tested the effects of the Sexunzipped website for sexual health compared to an information-only website. This study reports on a qualitative evaluation of the trial procedures, describing participants' experiences and views of the Sexunzipped online trial including methods of recruitment, incentives, methods of contact, and sexual health outcome measurement. ObjectiveOur goal was to determine participants' views of the acceptability and validity of the online trial methodology used in the pilot RCT of the Sexunzipped intervention. MethodsWe used three qualitative data sources to assess the acceptability and validity of the online pilot RCT methodology: (1) individual interviews with 22 participants from the pilot RCT, (2) 133 emails received by the trial coordinator from trial participants, and (3) 217 free-text comments from the baseline and follow-up questionnaires. Interviews were audio-recorded and transcribed verbatim. An iterative, thematic analysis of all three data sources was conducted to identify common themes related to the acceptability and feasibility of the online trial methodology. ResultsInterview participants found the trial design, including online recruitment via Facebook, online registration, email communication with the researchers, and online completion of sexual health questionnaires to be highly acceptable and preferable to traditional methods. Incentives might assist in recruiting those who would not otherwise participate. Participants generally enjoyed taking part in sexual health research online and found the questionnaire itself thought-provoking. Completing the sexual health questionnaires online encouraged honesty in responding that might not be achieved with other methods. The majority of interview participants also thought that receiving and returning a urine sample for chlamydia testing via post was acceptable. ConclusionsThese findings provide strong support for the use of online research methods for sexual health research, emphasizing the importance of careful planning and execution of all trial procedures including recruitment, respondent validation, trial related communication, and methods to maximize follow-up. Our findings suggest that sexual health outcome measurement might encourage reflection on current behavior, sometimes leading to behavior change. Trial RegistrationInternational Standard Randomized Controlled Trial Number (ISRCTN): 55651027; http://www.controlled-trials.com/isrctn/pf/55651027 (Archived by WebCite at http://www.webcitation.org/6LbkxdPKf).